2020
DOI: 10.1101/2020.04.26.20080408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negative regulation ofACE2by interferonsin vivoand its genetic control

Abstract: The SARS-CoV-2 pandemic has resulted in widespread morbidity and mortality globally. ACE2 is a receptor for SARS-CoV-2 and differences in expression may affect susceptibility to COVID-19. Using HCV-infected liver tissue from 195 individuals, we discovered that among genes negatively correlated with ACE2, interferon signalling pathways were highly enriched and observed down-regulation of ACE2 after interferon-alpha treatment. Negative correlation was also found in the gastrointestinal tract and in lung tissue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(93 reference statements)
1
5
0
Order By: Relevance
“…Although the mouse and human ACE2 and TMPRSS2 expression data align nearly perfectly in the olfactory epithelium (Brann et al, 2020), there may be clinically relevant divergences between species in the olfactory bulb and brain (Hodge et al, 2019;Maresh et al, 2008). Finally, it is important to note that the ACE2 gene is regulated by inflammation in human cells, and other SARS-CoV-2 entry genes may be similarly modulated by primary infection and inflammation (Ansari et al, 2020;Ziegler et al, 2020). This observation raises the possibility that a broader spectrum of cells expresses ACE2 during SARS-CoV-2 infection than is currently appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mouse and human ACE2 and TMPRSS2 expression data align nearly perfectly in the olfactory epithelium (Brann et al, 2020), there may be clinically relevant divergences between species in the olfactory bulb and brain (Hodge et al, 2019;Maresh et al, 2008). Finally, it is important to note that the ACE2 gene is regulated by inflammation in human cells, and other SARS-CoV-2 entry genes may be similarly modulated by primary infection and inflammation (Ansari et al, 2020;Ziegler et al, 2020). This observation raises the possibility that a broader spectrum of cells expresses ACE2 during SARS-CoV-2 infection than is currently appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that many cell types respond to IFN-I with varying transcriptional responses [ 25 ]. Thus, the ability of IFN-I to increase the expression of different ISGs including ACE2 can vary widely depending on the different cell type composition of the respiratory sample analyzed [ 13 , 14 ]. Furthermore, our data confirmed that flACE2 did not increase after IFNβ treatment [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we hypothesized that CF patients might exhibit a differential expression of ACE2, furin and TMPRSS2 in the upper respiratory tract cells, which might impact on the SARS-CoV-2 infection and/or spread. Moreover, as there are contrasting results on the relationship between IFN-I and ACE2 isoforms expression [ 13 , 14 ], we aimed to study the relationship of ACE2 (all isoforms), furin and TMPRSS2 with IFN stimulated gene 15 (ISG15), a well-established ISG that acts as a potential modifier of CF severity, as well as ACE2 responsiveness to ex vivo IFN-I stimulation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of RNA virus infection, ACE2 expression shows a significant negative correlation with IFN pathway genes. One of these SNPs is located near a frameshift mutation that disables the production of IFN-l4 (Ansari et al, 2020). As both ACE2 and receptors for IFN-l are preferentially expressed on type II alveolar pneumocytes, their association may be relevant in COVID-19 pathology, as suppressed IFN-l expression coupled with elevated ACE2 expression could simultaneously suppress epithelial defense while amplifying the viral load.…”
Section: Weak Interferon Defense and Neutrophil-driven Cytotoxicity Imentioning
confidence: 99%